Detection and Analytical Capabilities for Trace Level of Carbon in High-Purity Metals by Laser-Induced Breakdown Spectroscopy with a Frequency Quintupled 213 nm Nd:YAG Laser - Masaki Ohata; Toshiki Nakae (Journal of Chemistry)
The laser-induced breakdown spectroscopy (LIBS) with a frequency quintupled 213 nm Nd:YAG laser was examined to the analysis of trace level of carbon (C) in high-purity metals and its detection and analytical capabilities were evaluated. Though C signal in a wavelength of 247.9 nm, which showed the highest sensitivity of C, could be obtained from Cd, Ti, and Zn ca. 7000 mg kg−1 C in Fe could not be detected due to the interferences from a lot of Fe spectra. Alternative C signal in a wavelength of 193.1 nm could not be also detected from Fe due to the insufficient laser output energy of the frequency quintupled 213 nm Nd:YAG laser. The depth analysis of C by LIBS was also demonstrated and the C in Cd and Zn was found to be contaminated in only surface area whereas the C in Ti was distributed in bulk. From these results, the frequency quintupled 213 nm Nd:YAG laser, which was adopted widely as a commercial laser ablation (LA) system coupled with inductively coupled plasma mass spectrometry (ICPMS) for trace element analysis in solid materials, could be used for C analysis to achieve simultaneous measurements for both C and trace elements in metals by LIBS and LA-ICPMS, respectively.